Building better brains: the pleiotropic function of neurotrophic factors in postnatal cerebellar development - Boxy, Pia; Nykjær, Anders; Kisiswa, Lilian (Frontiers in Molecular Neuroscience, 2023)
The cerebellum is a multifunctional brain region that controls diverse motor and non-motor behaviors. As a result, impairments in the cerebellar architecture and circuitry lead to a vast array of neuropsychiatric and neurodevelopmental disorders. Neurotrophins and neurotrophic growth factors play essential roles in the development as well as maintenance of the central and peripheral nervous system which is crucial for normal brain function. Their timely expression throughout embryonic and postnatal stages is important for promoting growth and survival of both neurons and glial cells. During postnatal development, the cerebellum undergoes changes in its cellular organization, which is regulated by a variety of molecular factors, including neurotrophic factors. Studies have shown that these factors and their receptors promote proper formation of the cerebellar cytoarchitecture as well as maintenance of the cerebellar circuits. In this review, we will summarize what is known on the neurotrophic factors’ role in cerebellar postnatal development and how their dysregulation assists in developing various neurological disorders. Understanding the expression patterns and signaling mechanisms of these factors and their receptors is crucial for elucidating their function within the cerebellum and for developing therapeutic strategies for cerebellar-related disorders.